Particle diffusion in a wave with randomly jumping phase - Zasenko, V.I.; Zagorodny, A.G.; Chernyak, O.M. (Вопросы атомной науки и техники, 2015)
Microwave radiation with random phase jumps attracts attention because of its ability to penetrate into the overdense plasma. Along with this the wave with jumping phase is involved into the resonance interaction with more particles than a regular wave, and can be used to accelerate and heat them. The evolution of statistical characteristics of particle ensemble in a wave is calculated numerically for two types of phase jumps, namely, when they are formed in the region of wave interaction with the particles, and when the wave with already generated phase jumps is launched into the interaction region. It is shown that the intensity of heating depends substantially on the type of phase jumps. Интерес к микроволновому излучению со случайными прыжками фазы обусловлен его способностью проникать в плазму с закритической плотностью. Кроме того, волна с прыжками фазы вступает в резонансное взаимодействие с бо́льшим количеством частиц, чем регулярная волна, и может быть использована для их ускорения и нагрева. Методом численного моделирования рассчитана эволюция статистических характеристик ансамбля частиц в поле волны для двух типов прыжков фазы, а именно: когда они образуются в области взаимодействия волны с частицами и когда волна с уже сгенерированными прыжками фазы вводится в область взаимодействия. Показано, что интенсивность нагрева частиц существенно зависит от типа прыжков фазы. Інтерес до мікрохвильового випромінення з випадковими стрибками фази обумовлений його здатністю проникати в плазму із закритичною густиною. Крім того, хвиля зі стрибками фази вступає в резонансну взаємодію з більшою кількістю частинок, ніж регулярна хвиля, і може застосовуватись для їхнього прискорення та нагрівання. Методом числового моделювання розраховано еволюцію статистичних характеристик ансамблю частинок у полі хвилі для двох типів стрибків фази, а саме: коли вони утворюються в області взаємодії хвилі з частинками і коли хвиля із вже згенерованими стрибками фази вводиться в область взаємодії. Показано, що інтенсивність нагрівання частинок істотно залежить від типу стрибків фази.